Signs of Deregulated Gene Expression Are Present in Both CD14+ and CD14- PBMC From Non-Obese Men With Family History of T2DM - Koc, Michal; Šiklová, Michaela; Šrámková, Veronika; Štěpán, Marek; Krauzová, Eva; Štich, Vladimír; Rossmeislová, Lenka (Frontiers in Endocrinology, 2021)
Aim Development of type 2 diabetes (T2DM) is associated with disturbances in immune and metabolic status that may be reflected by an altered gene expression profile of peripheral blood mononuclear cells (PBMC). To reveal a potential family predisposition to these alterations, we investigated the regulation of gene expression profiles in circulating CD14+ and CD14- PBMC in fasting conditions and in response to oral glucose tolerance test (OGTT) in glucose tolerant first-degree relatives (FDR) of T2DM patients and in control subjects. Materials and Methods This work is based on the clinical study LIMEX (NCT03155412). Non-obese 12 non-diabetic (FDR), and 12 control men without family history of diabetes matched for age and BMI underwent OGTT. Blood samples taken before and at the end of OGTT were used for isolation of circulating CD14+ and CD14- PBMC. In these cells, mRNA levels of 94 genes related to lipid and carbohydrate metabolism, immunity, and inflammation were assessed by qPCR. Results Irrespectively of the group, the majority of analyzed genes had different mRNA expression in CD14+ PBMC compared to CD14- PBMC in the basal (fasting) condition. Seven genes (IRS1, TLR2, TNFα in CD14+ PBMC; ABCA1, ACOX1, ATGL, IL6 in CD14- PBMC) had different expression in control vs. FDR groups. OGTT regulated mRNA levels of nine genes selectively in CD14+ PBMC and of two genes (ABCA1, PFKL) selectively in CD14-PBMC. Differences in OGTT-induced response between FDR and controls were observed for EGR2, CCL2 in CD14+ PBMC and for ABCA1, ACOX1, DGAT2, MLCYD, and PTGS2 in CD14- PBMC. Conclusion This study revealed a different impact of glucose challenge on gene expression in CD14+ when compared with CD14- PBMC fractions and suggested possible impact of family predisposition to T2DM on basal and OGTT-induced gene expression in these PBMC fractions. Future studies on these putative alterations of inflammation and lipid metabolism in fractionated PBMC in larger groups of subjects are warranted.